CONCEPT OF ELECTION SYSTEM AND ITS CHARACTERISTICS - Федорів, Х. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article reveals the essence of the concept of the electoral system and considered its basic types: majoritarian, proportional and mixed systems with their characteristics and examples of application.